2015
DOI: 10.17116/hirurgia2015263-69
|View full text |Cite
|
Sign up to set email alerts
|

The results of combined ozone therapy using in complex treatment of soft tissues infections in patients with diabetes mellitus type II

Abstract: Levels of interleukins-6, 8, 10, TNF-alpha and basic fibroblast growth factor (bFGF) were examined in peripheral blood of 60 patients with diabetes mellitus type II and soft tissues infections. It was revealed the elevated levels of proinflammatory (IL-6, 8), anti-inflammatory (IL-10) cytokines and basic fibroblast growth factor at the time of admission. Application of combined ozone therapy including ozonated autohemotherapy and superficial management of wounds with ozone-oxygen mixture resulted in significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Ozone therapy has also demonstrated the ability to inhibit the production of cytokines such as IL-6 and TNF-α. Lower levels of these cytokines are beneficial for promoting the healing and repair of wounds ( 26 , 27 ). Supporting our findings, our study also demonstrated lower levels of IL-6 and TNF-α in the ozone therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone therapy has also demonstrated the ability to inhibit the production of cytokines such as IL-6 and TNF-α. Lower levels of these cytokines are beneficial for promoting the healing and repair of wounds ( 26 , 27 ). Supporting our findings, our study also demonstrated lower levels of IL-6 and TNF-α in the ozone therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 53 ] Systemic OT can decrease IL-6 and other pro-inflammatory cytokines. [ 54 ] It has also been measured in vivo that the release of numerous cytokines from ozonated blood, at a concentration between 30 and 55 μg/mL, causes an increase in interferon production and less production of tumor necrosis factor α[ 55 ] and IL-2. [ 56 ]…”
Section: Discussionmentioning
confidence: 99%
“…It can be used effectively in both gram negative and gram positive bacteria, virus and fungal infections [15,16]. The mechanism of action of ozone oil provides skin oxygenation, increases microcirculation, triggers tissue repair and regeneration, slows the skin aging process.…”
Section: Discussionmentioning
confidence: 99%